PERSEPSI PESERTA DIDIK TERHADAP PEMBELAJARAN GEOGRAFI SECARA LURING DAN DARING PADA SMA NEGERI DI KOTA BONTANG - Lathifah, Eka Auliya; Setyasih, Iya'; Saputra, Yulian Widya (Jurnal Swarnabhumi : Jurnal Geografi dan Pembelajaran Geografi, 2022)
Learning geography carried out using offline and online methods will lead to different perceptions. Perception arises because students experience and directly observe geography learning which is carried out offline and online. This study aims to (1) determine students' perceptions of online geography learning at State Senior High Schools in Bontang City, and (2) determine students' perceptions of online geography learning at State Senior High Schools in Bontang City. This research is a type of descriptive research with a quantitative approach. The population in this study were students of class XII Social Sciences SMA Negeri Bontang with a population of 265 students using the Cluster Random Sampling sampling technique with a sample of 79 students. Data collection techniques in this study were interviews and questionnaires. The results showed that some of the students' perceptions of offline geography learning at State Senior High Schools in Bontang City stated strongly agree with the number of 47 students (59%), and students' perceptions of online geography learning at State Senior High Schools in Bontang City stated that they agreed with total 46 students (58%). Based on these results, there is a tendency that students prefer if learning is done offline, because students understand the material better and can interact directly with the teacher and their friends.